The influence of innovation capabilities on individual performance in the Interior Ministry of United Arab Emirates Government - Obaid Alhefeiti, Hamdan Sohail (2020)
Innovation capabilities of employees considered as vital practices in organizations to improve individual performance. Previous studies have identified and outlined the potential of organisations to exhibit different transformation in innovation but these studies were not focused on the innovation capabilities of individuals with respect to the betterment of their performance. This study first aimed to identify whether employees’ innovation capabilities in the Interior Ministry would exhibit better performance in the United Arab Emirates (UAE). Secondly, this study also aimed to identify the theoretical issues related to cultural and technological diversity with individual innovation capabilities and gave suggestions for improvement of performance in the Interior Ministry of UAE. This study proposes a conceptual framework for understanding the relationship between strategic planning, leadership management, capability development, innovation process and knowledge management as aspects of innovation capabilities and individual performance. In addition, the study utilizes technological and cultural diversity as mediating variables in the effect of innovation capability on individual performance. The conceptual framework is carried out through an empirical review of literature and development of hypotheses. A wellstructured questionnaire is used in this study. The study also validates the proposed conceptual framework using a quantitative approach through second-order confirmatory factor analysis technique, namely, structural equations modelling, with the data collected from 607 respondents from six departments of the Interior Ministry in the UAE. The findings suggest that innovation capabilities has a significant positive impact on individual performance. Moreover, technological and cultural diversity have a partial mediation effect on the relationship between innovation capability and individual performance. This study contributes to the research that identifies the influence of innovation capabilities on individual performance; this influence can affect organisational performance, particularly in the context of departments of the Interior Ministry in the UAE.